2017
DOI: 10.1098/rsob.160292
|View full text |Cite
|
Sign up to set email alerts
|

Structural, mechanistic and functional insight into gliotoxin bis -thiomethylation in Aspergillus fumigatus

Abstract: Gliotoxin is an epipolythiodioxopiperazine (ETP) class toxin, contains a disulfide bridge that mediates its toxic effects via redox cycling and is produced by the opportunistic fungal pathogen Aspergillus fumigatus. Self-resistance against gliotoxin is effected by the gliotoxin oxidase GliT, and attenuation of gliotoxin biosynthesis is catalysed by gliotoxin S-methyltransferase GtmA. Here we describe the X-ray crystal structures of GtmA-apo (1.66 Å), GtmA complexed to S-adenosylhomocysteine (1.33 Å) and GtmA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 52 publications
3
53
0
Order By: Relevance
“…To our knowledge, this is the first report of an in vivo interaction between gliotoxin biosynthesis, dysregulated DTG presence and growth inhibition due to potential interference with Zn 2+ -associated growth systems. Moreover, it contributes to explaining the cryptic observation of Dolan et al that A. fumigatus DgliT::DgtmA is the most gliotoxinsensitive mutant observed to date, 15 and also why there are two distinct enzymatic activities which can prevent intracellular DTG accumulation. Overall, these data indicate the inhibitory potential of this endogenous, and potent, Zn 2+ chelator in A. fumigatus in particular, and possibly microorganisms in general.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first report of an in vivo interaction between gliotoxin biosynthesis, dysregulated DTG presence and growth inhibition due to potential interference with Zn 2+ -associated growth systems. Moreover, it contributes to explaining the cryptic observation of Dolan et al that A. fumigatus DgliT::DgtmA is the most gliotoxinsensitive mutant observed to date, 15 and also why there are two distinct enzymatic activities which can prevent intracellular DTG accumulation. Overall, these data indicate the inhibitory potential of this endogenous, and potent, Zn 2+ chelator in A. fumigatus in particular, and possibly microorganisms in general.…”
Section: +mentioning
confidence: 99%
“…9,13,14 Methylation of dithiol holomycin has been proposed as a back-up plan for self-protection, and Dolan et al revealed that A. fumigatus DgliT::DgtmA is significantly more sensitive to exogenous gliotoxin than a gliT-deficient mutant. 15 This suggests that the combined absence of both self-protection and negative regulation of DTG biosynthesis (or its intracellular presence) results in potent growth retardation -the precise cause of which is unknown. 10,15 Gliotoxin, other ETPs and dithiolopyrrolones have been shown to inhibit the activity of many enzymes, and functionality of specific proteins.…”
Section: -8mentioning
confidence: 99%
See 1 more Smart Citation
“…Plates were incubated statically at 37°C for 48 h. Mycelia were visualized by both differential interference microscopy and fluorescence microscopy using an Olympus Fluo View 1,000 Laser Scanning microscope, as per Dolan et al (2017). …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, we contend that the discovery of EGT may necessitate reconsideration of previous studies pertaining to the oxidative stress sensitivity of A. fumigatus, and possibly other fungi, following deletion of reactive oxygen species (ROS)-dissipating systems (Lessing et al, 2007;Lambou et al, 2010). We then move to reveal and illustrate that both gliotoxin and EGT biosynthesis (Sheridan et al, 2016;Dolan et al, 2017) has led to molecular rewiring in A. fumigatus, whereby Cys, GSH and SAM have become substrates for the biosynthesis of the aforementioned metabolites, along with playing a role in gliotoxin 'activation' and attenuation, leading to unexpected consequences for fungal metabolic systems (Owens et al, 2015). Finally, we introduce the concept of a 'cystathionine switch' in A. fumigatus which may play a role in fluxing thiol-containing metabolites toward different fates, depending on the prevailing cellular redox homeostatic requirements (Sheridan et al, 2016).…”
Section: Introductionmentioning
confidence: 95%